Biography of Masutatsu Oyama - Góźdź, Joanna (Difficult situation in biographies: Volume 9, 2025)
Masutatsu Oyama was born in 1923 in Korea. In 1938, he emigrated to Japan to train as a pilot. He trained various martial arts, but after the post-war crisis he decided to devote his entire life to one of them – Karate. From 1952 he traveled – initially around the United States, then around the world, giving shows of this art. He fought over 200 fights with opponents representing various combat sports (he won all of them), defeated 52 bulls, also gave tamashiwari shows, and trained FBI officers. Ultimately, he created his own, the hardest style – Kyokushin Karate, which he spread all over the world and for his students, he created „100-kumite” test. He also left numerous publications on karate, which are some of the most widely read books on martial arts.